Psychomotor performance in video games - Krzysztof Horoszkiewicz; Bartosz Horoszkiewicz; Grzegorz Załęski (Kazimierz Wielki University, 2022)
Introduction: Interactive electronic games allow to access virtual environments and interact using a computer or TV screen. Anyone who has played a video game, or seen others playing, is aware of the importance of reaction speed and eye-hand coordination skills. Objective: To determine the differences in psychomotor performance between professional gamers and amateurs. Material and Methods:  A total of 62 gamers took part in the study, including 31 people - professional video game users who had participated in e-tournaments in the last month (age: M = 20.6, SD = 6.3) and 31 people who did not play video games or played very rarely (they declared that they did not participate in e-sports tournaments), who constituted the control group (age: M = 17.9, SD = 5.4). Integrated computer SDP-System with an executive module for stimulus generation and reception was used to assess psychomotor performance. Results: Professional gamers have higher psychomotor skills than amateurs. They reveal better results for fast thinking, motor reactions, perception, attention, and working memory. Conclusion: Playing video games has a positive impact on players' psychomotor performance and can promote improvements in elementary cognitive functions. Key words: video-games; e-sport; psychomotor performance; cognitive functions